AN INTEGRATED MACHINE LEARNING AND SOCIAL MEDIA MARKETING FRAMEWORK FOR ENHANCED CUSTOMER UNDERSTANDING AND DIGITAL MARKETING EFFICACY - Sanjeev Kumar,Dr. Alok Ranjan Tripathy, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The digital marketing landscape is increasingly driven by data, with social media platformsgenerating vast amounts of unstructured customer data. Understanding this data is critical fororganizations to tailor their strategies effectively. This research proposes a novel framework,Machine Learning-coordinated Social Media Marketing (ML-SMM), to analyze the variables that explain customers' understanding of digital marketing and the associated technologies. Themethodology integrates text mining of social media data